Using Digital Tools to Teach Soft Skill-Oriented Subjects to University Students during the COVID-19 Pandemic - Aleksandr Volkov; Yury Rishko; Yury Kostyukhin; Elena Sidorova; Diana Boboshko; Darya Savinova; Veronika Ershova (MDPI AG, 2022)
Radical changes in education occurred in 2020 during the pandemic. The need to fully switch to a distance-learning mode required rethinking the approaches to the organization of the learning process. Despite the fact that Russian universities were already using digital learning tools quite extensively at the beginning of the pandemic-those were seen as auxiliary, supporting tools. Within a short period, online learning made it necessary to design educational programs from a digital-technologies viewpoint, as traditional teaching methods had lost some of their functionality in the distance-learning mode. First of all, the changes affected the disciplines focused on the formation of soft skills, such as communication skills, group interaction, and managing people. Another problem of digitalization of all aspects of our lives is the huge amount of readily available information. In this regard, developing the students' systemic thinking and augmenting their ability to find and properly use information became an important alternative to acquisition of factual knowledge. This article summarizes the experience of the educational process at one of the leading Russian universities, National University of Science and Technology (NUST) "MISIS" during the COVID-19 pandemic based on the analysis of the degree of application of digital tools in online and hybrid learning. In this article, we present the description of methodology approaches to the use of digital tools for soft skill development, using the example of teaching specific disciplines "Systems Thinking and Theory of Constraints" and "Life Cycle of Corporations and Change Management" in the master's program in Corporate Finance taught at NUST "MISIS".